Evaluating adherence to medication in children and adolescents with HIV. Issue 12 (31st August 2009) - Khan, M; Song, X; Williams, K; Bright, K; Sill, A; Rakhmanina, N
Abstract : Objective: The study was aimed to evaluate the relationship between pharmacy supply, self-reported treatment adherence and HIV viral load in HIV-infected children. Methods: A retrospective (52 weeks) cohort study was conducted through the review of the existing databases. Pharmacy supply was classified as "home delivery" when the medications were delivered home and as "in pharmacy pick-up" when they were picked up at the pharmacy. Adherence was assessed through retrospective (3 days recall) self-report. Fisher's exact model, univariate and multivariate logistic regression analyses were used. Settings: The study collected data on 140 HIV-infected children (<18 years). Adherence, pharmacy supply information and HIV viral loads were obtained from clinical and research databases. Patients: The data from 127 HIV-infected children (60 boys and 67 girls; mean age 9.9 years) were collected. Main Outcome Measures: Complete adherence (100%) was reported in only 24% of patients. With 40% of patients being rarely or never completely adherent, 64% of children achieved undetectable viral loads during the study period. Results: No association between pharmacy supply and self-reported adherence was found (p = 0.605). Self-reported adherence (p = 0.0328) and age (p = 0.025) were the significant predictors of reaching undetectable viral loads. Adolescents (>13 years) were significantly less likely to reach undetectable viral loads than children under 13 years (odds ratio 0.38; 95% CI 0.16 to 0.89). Conclusion: In our study, pharmacy supply was not associated with self-reported adherence. Most importantly, adherence and age were significant predictors of reaching undetectable viral loads.